Social capital, human capital and fertility - Raffaella Coppier; Fabio Sabatini; Mauro Sodini (Economics and Econometrics Research Institute (EERI), 2018)
We develop an overlapping generations model to study how the interplay between social and human capital affects fertility. In a framework where families face a trade-off between the quantity and quality of children, we incorporate the assumption that social capital plays a key role in the accumulation of human capital. We show how the erosion of social capital can trigger a chain of reactions leading households to base their childbearing decisions on quantity, instead of quality, resulting in higher fertility.
Keywords: J13; Z1; Z13; 330; fertility; quantity-quality trade-off; human capital; education; social capital; trust